Architecting the 'third teacher': Solid foundations for the participatory and principled design of schools and (built) learning environments. (3rd July 2017) - Hall, Tony
Abstract: This issue of the European Journal of Education examines a crucially important, though largely overlooked, area in educational design research: architecting and building physical educational environments. Effective policymaking in school design necessitates the negotiated, shared and timely input of key educational stakeholders, including policymakers, architects, educational designers, pupils, teachers, and parents. Furthermore, practical, participatory and principled examples of the design and construction of bespoke learning spaces are warranted to guide those formulating and implementing policy, particularly the commissioning and construction of built educational environments. The articles exemplify how to engage diverse, key stakeholders in participatory design of school buildings, whilst practically illustrating design innovations in context. This commentary article offers reflections on the respective articles, informed by extant, relevant research on the history and praxis of school building design internationally. This includes the Reggio Emilia Schools' socio‐material concept of 'the third teacher', a philosophy that is particularly germane to the participatory design of contemporary (built) learning environments. The article concludes with design sensitivities and SEAM framework ( space, engagement, aestheticity and media ), which can be used to explore and extend further the concepts, methods and technologies outlined in this issue.